1998
DOI: 10.3758/bf03206038
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory processes in auditory selective attention: Evidence of location-based and frequency-based inhibition of return

Abstract: The possibility that there is an inhibitory component to auditory covert orienting was addressed. Each trial consisted of a cue followedby a target, and listeners were required to detect, localize,or identify the frequency of the target. At 150-msecstimulus onset asynchrony (SOA), performance was best when stimuli sounded from the same location or were of the same frequency. However, at 750-msec SOA, performance was best when stimuli differed in location or were of different frequencies. These results document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
67
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 40 publications
16
67
1
Order By: Relevance
“…For instance, Mondor and Bregman (1994) found that a valid frequency cue improved performance on a duration discrimination task for ISIs up to 1500 ms. A similar facilitation for validly cued frequencies has been reported for other orthogonal tasks, such as intensity discrimination (Mondor & Lacey, 2001;Ward, 1997;Ward & Mori, 1996) and rise-time discrimination (Mondor, Zatorre, & Terrio, 1998). Attention has also been given to determining the time course of this facilitation and under what circumstances it reverses to inhibition with longer ISIs (Mondor, Breau, & Milliken, 1998;Mondor, Hurlburt, & Gammell, 2003;Prime & Ward, 2002). …”
Section: Attention To Auditory Frequency-supporting
confidence: 58%
“…For instance, Mondor and Bregman (1994) found that a valid frequency cue improved performance on a duration discrimination task for ISIs up to 1500 ms. A similar facilitation for validly cued frequencies has been reported for other orthogonal tasks, such as intensity discrimination (Mondor & Lacey, 2001;Ward, 1997;Ward & Mori, 1996) and rise-time discrimination (Mondor, Zatorre, & Terrio, 1998). Attention has also been given to determining the time course of this facilitation and under what circumstances it reverses to inhibition with longer ISIs (Mondor, Breau, & Milliken, 1998;Mondor, Hurlburt, & Gammell, 2003;Prime & Ward, 2002). …”
Section: Attention To Auditory Frequency-supporting
confidence: 58%
“…For example, Francis and Milliken (2003) described two forms of nonspatial IOR in vision based on stimulus length and color. Mondor, Breau, and Milliken (1998) found evidence for frequency-based auditory IOR. More recently, Morgan and Tipper (2007) have described a shape-specific version of IOR.…”
Section: Converging Evidencementioning
confidence: 99%
“…More recently, Morgan and Tipper (2007) have described a shape-specific version of IOR. Although these researchers did not refer to these effects as habituation, it is part of a trend of studies that have attempted to apply the concept of IOR to nonspatial dimensions (Grison, Paul, Kessler, & Tipper, 2005;Mondor & Breau, 1999;Mondor et al, 1998;Mondor & Lacey, 2001;Prime & Ward, 2002;Riggio, Patteri, & Umiltà, 2004). As I see it, there is an intuition growing among attention researchers that IOR represents a more general mechanism of attentional suppression.…”
Section: Converging Evidencementioning
confidence: 99%
“…IOR is also known to 'follow' objects as they move around the environment as well as being tagged to fixed spatial locations (Abrams & Dobkin, 1994;Tipper, Driver, & Weaver, 1991). Finally, it is crossmodal, having been shown to occur within and between the visual, auditory and tactile domains (Mondor, Breau, & Milliken, 1998;Poliakoff, Spence, O'Boyle, McGlone, & Cody, 2002).…”
Section: Inhibition Of Returnmentioning
confidence: 99%